IDENTIFYING RISK FACTORS RELATED TO PROGRESSIVE KIDNEY FAILURE IN HIGHHEMATOCRIT, NORMAL-HEMOGLOBIN DIABETES PATIENTS SEEN IN SURIN HOSPITAL IN THAILAND - Sueyanyongsiri , Passorn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Diabetes is now the most common cause of end-stage renal disease (ESRD). This research aims to study the rate of decline in estimated glomerular filtration rate (eGFR) and risk factors related to progressive renal failure in highhematocrit, normal-hemoglobin diabetic patients in Surin Hospital, Thailand. METHODOLOGY This case-control cohort study was conducted from 2009 to 2020. The patients’ general clinical information, fasting plasma glucose (FPG), HbA1c levels, hematocrit (Hct), and eGFR were collected and divided into two groups; hematocrit higher than 42% (study group) and normal hematocrit level (hematocrit 36.1-40.0%, control group). The patients with confirmed diabetes were treated either with insulin, oral hypoglycemic drugs, or a physicianprescribed diet. The target of diabetes control follows standard treatment, not intensive control. The endpoint was a rate of decline of eGFR per year. The hypothesis was that the cumulative average duration of disease was equal, and the renal complications between the two groups were not different. RESULTS From 2009 to 2020, there were 216 diabetic patients with 108 males (50%) included. A total of 1870 blood tests were done, 1248 (67%) in the study group and 622 (33%) in the control group. There were no significant differences concerning mean cholesterol (CHO) among the groups. The mean age and eGFR were significantly lower in the study group. The males in the study group had significantly higher mean systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), serum creatinine (Cr), and duration of disease were significantly higher. The rate of decline in eGFR was significantly slower in the control group, at -0.134 ml/min/year (p <0.689) and -0.778 ml/min/year in the study group (p <0.008). CONCLUSION In a long-term cohort study, the high-hematocrit and normal-hemoglobin groups had faster progression torenal failure. Diabetic patients with high hematocrit levels should be monitored using HbA1c levels as an indicator for long-term glycemic control and may need intensive risk control.